O-01 Planning for parental death and transitions in care for older people with learning disabilities: An adapted experience-based co-design project. (19th November 2022) - Keagan-Bull, Richard; Anderson, Rebecca; Giles, Jo; Tuffrey-Wijne, Irene
Abstract : Introduction: Around two thirds of the 900, 000 learning-disabled adults in the UK live with parent(s). Parents have expressed fears about what will happen to their sons and daughters when they die. Aims: To understand families' concerns about the future. To develop resources to help families plan for parental death. Method: An adapted Experience Based Co-Design approach: Interviews with 37 people including: learning-disabled adults (40+) living with parent(s); parents; and siblings. A film about participants' experiences. Twelve co-design group meetings to design future-planning resources. The co-lead authors of this paper are a learning-disabled researcher and his non-learning disabled colleague, who planned and conducted this study together. Results: Parents' main end-of-life concerns were what would happen to their adult children. They could not consider advance care plans without first planning for their sons and daughters. Siblings often struggled to talk to their parents about what would happen after they die, and felt a lack of control over future plans. Some learning-disabled adults saw living away from parents as an opportunity to gain independence, but others worried support staff would limit their opportunities to do the things they love. The co-design group created conversation cards to help families plan for the future. This included cards to help think about support needs and preparations for conversations with social workers. They created a set of cards called 'illness, death and dying'. These included prompts to talk about what would happen when parents get ill. Conclusion: For parents of learning-disabled adults, ensuring their son's or daughter's wellbeing is the priority for advance care planning. Focusing on the impact of end-of-life decisions on loved ones is not unique to this group, but it does require additional input from professionals, particularly social services. Enabling families to make plans helps them to live well now, without fears about what will happen after parents die.